Land Planarians, Bipalium kewense Moseley and Dolichoplana striata Moseley (Tricladida: Terricola) - P.M. Choate; R.A. Dunn (EDIS)
This document provides an overview of land planarians, specifically Bipalium kewense and Dolichoplana striata. It covers their distribution, physical description, reproduction, habitat, locomotion, nutrition, and economic importance. The species are noted for their disjunct distribution, preference for high humidity, and predatory behavior towards earthworms. The article also highlights their spread through horticultural practices and their presence in various regions, including the United States. Additionally, it mentions the challenges in managing these species and their limited impact on disease transmission. Original publication date August 1998.